Does NTPC Have a Dominant Position? A Critical Analysis. (December 2014) - Gangakhedkar, Rajesh; Mishra, R.K.
The past two decades have witnessed huge changes in the electricity sector. The changes in this sector at a rapid pace world over have resulted in competition in some segments of the sector, such as, generation and in some cases in distribution. India is no exception to the reforms that are being undertaken. The provisions of Open Access, power trading, competitive bidding, mentioned in the Electricity Act of 2003 are expected to give a spurt to competition. The favourable impact of all these factors includes wide choice of electricity suppliers for consumers and electricity at cheaper rates, which is in fact one of the cherished goals of reforms in the sector. However, it is not necessary that competitive markets would produce competitive results. There could be significant distortions in the form of anti-competitive behaviour, which would get manifested in the form of collusions, abuse of dominant position, etc. Experiences of some countries reveal that anti-competitive behaviour of various players in the power sector is not very uncommon. In India also there are controversies regarding the provision of Open Access, which are pointer towards an anti-competitive conduct. There are also apprehensions regarding abuse of dominant position by some companies. The primary objective of this article is to examine whether NTPC Ltd., which is the largest power generating company in India, has a dominant position in the power sector. The article also discusses the possible ways in which a dominant power-generating company could abuse its position. The study is conceptual in nature and draws heavily from the secondary sources of information. The study uses two tools: Herfindahl–Hirschman Index (HHI) and Residual Supply Index (RSI).